2009
DOI: 10.1504/ijbsr.2009.027200
|View full text |Cite
|
Sign up to set email alerts
|

A study of the selection criteria for enterprise resource planning systems

Abstract: This study draws on the findings of two cross-sectional surveys of the top 5,000 largest corporations in Taiwan, undertaken in 2003 and 2006. It presents the organisations' criteria for selecting enterprise resource planning (ERP) software package and its supplier. The different selection criteria for ERP software package and its supplier between the two investigative years are discussed. From the results, we also discovered that a number of selection criteria are highly related to a domestic or international … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…FourchangesmayimpacttherankingofdifferentfactorsinfluencingthechoiceofanERP type over time (Garrison, Wakefield, & Kim, 2015;Tsai, Lee, Chen, & Hsu, 2009;Tsai, Lee, Shen,&Lin,2012):userexperienceschanges,technologychanges,userrequirementschanges, andeconomicalchanges.…”
Section: Resultsmentioning
confidence: 99%
“…FourchangesmayimpacttherankingofdifferentfactorsinfluencingthechoiceofanERP type over time (Garrison, Wakefield, & Kim, 2015;Tsai, Lee, Chen, & Hsu, 2009;Tsai, Lee, Shen,&Lin,2012):userexperienceschanges,technologychanges,userrequirementschanges, andeconomicalchanges.…”
Section: Resultsmentioning
confidence: 99%
“…The review results are summarized and were intended as a source for software selection problems. Tsai et al [41] have surveyed the selection of ERP software packages and its supplier in Taiwan industries. The survey was performed in 5,000 largest corporations between 2003 and 2006.…”
Section: Related Workmentioning
confidence: 99%
“…The measurement is observation and quantification while evaluation is a paired measurement with an observation of what would be desired and comparison is putting two evaluations against each other [43]. Although performance measurement and evaluation are ensuring the successful implementation of information systems, also ERP model consists of data models, Critical Success Factor (CSF) models and phase models [44], evaluation ERP solutions in post-implementation phase is under-research [33].In [30], [45] previewed some researches that discussed the relation between criteria of ERP selection and enterprise's size and concluded that the size does not significantly affect criteria selection, but only on the judgment importance assigned in comparisons. For example, flexibility and supplier support are two first selection criteria in large-sized enterprise, however cost and adoptability are the most important criteria for smallmedium sized enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are different models are produced to select and evaluate ERP systems. [45] Collected eight models from 1997 until 2006 and studied the dependency between selection criteria of ERP packages and ERP vendors. [31] Used the criteria of updated DeLone & McLean of success IS model, apply hybrid MCDM process (AHP and TOPSIS) on it to detect that service quality is a best criterion (with its sub-criteria: on time delivery, knowledge and competency, error network, availability, access, rate delay and reliability) for two different IS in banking and construction industry sector.…”
Section: Literature Reviewmentioning
confidence: 99%